Efisiensi Kapasitas dan Biaya Produksi Kerupuk Ikan melalui Penggunaan Mesin Pengadonan pada UKM Maharani - Muhamad Firdaus; Candra Adi Intyas (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Making the dough is a critical point in the production of fish crackers. Target partners in making the dough by hand, so that the resulting production capacity is low, the texture is not uniform and the price is cheap. The purpose of this activity is to provide skills to use the dough machine to the target partners, improve product characteristics, and increase the capacity and cost efficiency of fish cracker production through the use of a dough machine. The target partner is Mrs. Siti Saroh, the owner of UKM. Maharani in Weru village, Paciran sub-district, Lamongan district. The specifications of the mixing machine used in this activity have as many as two moving stirring spoons and the driving machine is in the form of an electric dynamo which is powered by ½ HP (370 Watt). The ingredients for making crackers are tapioca flour, a mixture of tonang fish and Balak fish, garlic, salt, sugar, and flavoring. This dedication method is in the form of training in the use of a dough machine to partners, product characterization and analysis of production cost efficiency. The results of this activity can improve partners' skills in using the dough machine, production capacity increases 87.5%, the product has a flatter surface, does not crack and when fried can expand 67%, and the efficiency of production costs by 84.64%. As a conclusion, the use of mixing machines can increase the capacity and cost efficiency of fish cracker production.